A course on adaptive and autonomous aerospace systems. Issue 12 (2021) - Invernizzi, Davide; Lovera, Marco
Abstract: In this paper we present the one-semester course "Adaptive and Autonomous aerospace Systems" to be taught to master students in aerospace engineering at Politecnico di Milano starting fall 2021. The paper discusses the course motivation and objectives, how it fits within the current study program in aerospace engineering, the course syllabus and organization and the learning assessment and outcomes. While being a fundamental course in character, covering the main theoretical aspects of adaptive and autonomous control, laboratory activities will complement the students learning by showing realistic implementations of the algorithms taught in class.